How Indonesia Students Define Enterpreneur Profession? - Rafiati Kania (The Indonesian Journal of Social Studies, 2021)
In 2018, the growth of Indonesian entrepreneur increased significantly from 1,6 % to 3,1 % over three years. In order to increase the number of entrepreneurs in Indonesia, entrepreneurship education at universities has an important role to foster interest in entrepreneurship. Drawing on entrepreneurship education literature, entrepreneurial mindset in students will be strength if education have ability to distinguish entrepreneurs from other profession.  This study aims to construct attributable to the particular self-concept which define entrepreneur profession characteristics. In testing how attributes forming profession characteristics, this study uses PLS-SEM to confirm the model. This study uses a sample of 303 undergraduate students participating in the educational setting that educate entrepreneurial mindset. Findings shows that self-concept defining entrepreneur profession include entrepreneurial creativity, opportunity recognition capability, and risk management capability.